2020
DOI: 10.1111/jce.14784
|View full text |Cite
|
Sign up to set email alerts
|

Very long‐term outcomes after catheter ablation of atrioventricular nodal reentrant tachycardia: How does cryoenergy differ from radiofrequency?

Abstract: Introduction: Either cryoenergy or radiofrequency can be used during atrioventricular nodal reentrant tachycardia (AVNRT) ablation. There are still limited data comparing their respective long-term efficacy (>1 year). This study sought to compare the very long-term outcomes of AVNRT ablation using radiofrequency or cryotherapy. Methods: We retrospectively included all patients who had undergone a first AVNRT ablation in our institution between January 2010 and December 2017. The primary endpoint was recurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…As mentioned in article, 1 we cannot provide a definite explanation for these late AVNRT recurrences.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…As mentioned in article, 1 we cannot provide a definite explanation for these late AVNRT recurrences.…”
mentioning
confidence: 78%
“…We gratefully thank the authors for their constructive comments on our article entitled Very long-term outcomes after catheter ablation of AVNRT: How does cryoenergy differ from radiofrequency? 1 In their letter, Insulander et al proposed an alternative explanation to our observation of very late recurrences following AVNRT ablation. In their own experience with cryoablation of AVNRT, they also documented late and very-late recurrences of arrhythmia.…”
mentioning
confidence: 83%
“…We read with great interest the recently published article by Chaumont et al (1) regarding late recurrences in AVNRT after cryoablation. The authors found that among 257 patients with AVNRT successfully ablated with cryo energy, recurrences occurred in 24 subjects during a follow-up of 38±27 months.…”
Section: Conflict Of Interest: Nonementioning
confidence: 97%
“…
We read with great interest the recently published article by Chaumont et al 1 regarding late recurrences in atrioventricular reentrant tachycardia (AVNRT) after cryoablation. The authors found This may also be explained by the previously mentioned age-related AV nodal changes.Consequently, the occurrence of AVNRT many years after an ablation procedure may perhaps not always implicate a recurrence but instead an arrhythmia caused by a new substrate.
…”
mentioning
confidence: 99%
“…We read with great interest the recently published article by Chaumont et al 1 regarding late recurrences in atrioventricular reentrant tachycardia (AVNRT) after cryoablation. The authors found This may also be explained by the previously mentioned age-related AV nodal changes.…”
mentioning
confidence: 99%